Sustained and non-sustained silent reading and students' reading comprehension - Nueva, Jeneifer C. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2015)
This study aimed to determine the reading comprehension level of students before exposure to SSR and non-SSR methods; identifying reading comprehension level of students after exposure to SSR and non-SSR methods; and compare the reading comprehension level of students exposed to SSR and non SSR methods. It used pretest-posttest quasi-experimental design consisting of two intact classes of 79 grade 9 students. One class was exposed to SSR with reflective reading journal and interaction while the other was exposed to non-SSR with no reflective journal reading and no interaction. The pretest revealed that students in both groups did not differ significantly in their mean scores. Both groups belonged to the frustration level. The result indicated that the respondents' performance in comprehension was the same before the conduct of SSR. The posttest revealed that there was an increase in the performance of students in both groups. However, the improvement was higher in the SSR group. The comparison of posttest results revealed that there is a significant difference in the comprehension level of the respondents between groups. The data proved that SSR significantly improved the reading comprehension of the students.